Sistem Pendukung Keputusan Penerapan Metode MOOSRA Rekrutmen PPNPN Pada Kantor Pertanahan Kota Medan - Fatiyah Saidah; Nelly Hasibuan; Elsa Pratiwi (SNASTIKOM, 2022)
An agency or company can develop well of course determined by the quality and competence of its employees In a government agency there are several types of employees, namely ASN / Non PNS and PNS (Civil Servants). ASN or Non PNS employees are Honorary Employees, employees recruited by government agencies. Acceptance of ASN / Non PNS candidates who have met the general requirements in admission (Recruitment) where criteria and weighting as a benchmark for a government agency in choosing the parameters of a determination pass. After fulfilling the requirements of the layman in determining prospective employees, it has the next stage, namely the administrative selection stage, written examination selection (CBT), Wawacara selection. But the number of submissions of prospective employee files that have met the requirements makes the selection process more difficult and takes a long time. Therefore, a decision support system is needed to be the solution of the feud so that the selection process is more effective with objective results in terms of determining non-civil servants in the medan city land office for the eligibility of new ASN or Non-CIVIL SERVANT employees. In this case the MOOSRA Method It is appropriate to use with the formulation of the usual decision matrix: alternatives, criteria, or attributes, individual weights or coefficient p of each criterion and measure performance in relation using criteria. It is appropriate to use with the formulation of the usual decision matrix: alternatives, criteria, or attributes, individual weights or coefficient p of each criterion and measure performance in relation using criteria. From the test results, the best alternative that is considered worthy of being a not-civil servant government employee at the medan city land office is alternative A8 on behalf of yudha with the best prevention value of 0.445 as the first rank.